Identification, Characterization and HPLC Quantification of Process-Related Impurities in Bepotastine Besilate Bulk Drug - Zhang, Chaowei; Han, Chengqun; Sun, Lili; Yu, Jinlong; Zou, Qiaogen (Drug Research, 2020)
Bepotastine besilate (here after referred to as BTST), chemically known as ({d(S)4[4[(4chlorophenyl) (2pyridyl) methoxy] piperidino} butyric acid monobenzene sulphonate), is a second-generation antihistamine drug. To the best of our knowledge, no studies concerning the isolation or identification of process-related impurities have been reported so far. The current study reports the development and validation of a stability-indicating RP-HPLC method for the separation and identification of 5 potential impurities in bepotastine besilate. In this experiment, the structures of 3 process-related impurities were found to be new compounds. They were characterized and confirmed by NMR and MS spectroscopy analyses. These 3 new compounds were proposed to be (S)-4-[(phenyl)-2-pyridinylmethoxy]-1-piperidinebutanoic acid,(Imp-A); 4-[(S)-(4-chlorophenyl)-2-pyridinylmethoxy]-1- piperidinebutyric acid, N-oxide (Imp-B) and (S)-4-[(4- chlorophenyl)-2-pyridinylmethoxy]-1-piperidylethane (Imp-C). In addition, an efficient optimized chromatographic method was performed on a Shimadzu Inertsil C8–3 column (150 mm×4.6 mm, 3 μm) to separate and quantify these 5 impurities. It was using 15 mmol ammonium formate buffer in water (pH adjusted to 3.8 with formic acid) and acetonitrile as the mobile phase in gradient mode. The method was developed to separate and quantify these 5 impurities obtained in the range of 0.05–0.75 μg/mL. It was validated and proven to be selective, accurate and precise and suitable. It is the first publication of identification and characterization data of the 3 new compounds. It is also the first effective HPLC method for separation and quantification of all of process-related impurities in bepotastine besilate.
Keywords: drug research; chemistry; anti-inflammatory drugs